Age Assessment: Polish Practice and International Standards (Polish Yearbook of International Law, 2023)
This article addresses the legal aspects of assessing the age of foreign minors. It is a juxtaposition of the development of international legal standards in this area with the law and practice of the Polish authorities. The basic thesis of this analysis is the statement that Polish law in its current form requires fundamental change with respect to at least three elements. First, it is necessary to extend the methods of age assessment to also include non-medical methods. Secondly, the law should clearly define the legal form in which the age of a foreigner is determined and, at the same time, impose an obligation to provide a foreigner with the results of the assessment. Thirdly, a person concerned should have a direct opportunity to appeal.